Cap and Trade Offsets: the Case for following RGGI’s Model Rule - Nathan Markey (Amsterdam Law Forum, 2010)
<!-- /* Font Definitions */ @font-face {font-family:Cambria; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:3 0 0 0 1 0;} @font-face {font-family:Garamond; panose-1:2 2 4 4 3 3 1 1 8 3; mso-font-charset:0; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:3 0 0 0 1 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin-top:0in; margin-right:0in; margin-bottom:10.0pt; margin-left:0in; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-ascii-font-family:Cambria; mso-fareast-font-family:"Times New Roman"; mso-hansi-font-family:Cambria; mso-bidi-font-family:"Times New Roman";} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.25in 1.0in 1.25in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --><!--StartFragment--> The cap-and-trade of pollutants is often seen as the most politically acceptable form of regulating pollutants, such as carbon dioxide (CO2), as it is seen as the lowest cost alternative of regulation, and allows for innovative market responses within the regulated framework to lower costs. One of the regulation mechanisms that can be used to allow for these market innovations within a cap-and-trade market is inclusion of offsets into the market’s framework. The Regional Greenhouse Gas Initiative Model Rule offset provisions use a standards based approach to offsets, addressing many of the potential issues with implementing an offsets program, providing an excellent model for developing offset provisions. <!--EndFragment-->